2017
DOI: 10.1016/j.juro.2016.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Causes, Timing, Hospital Costs and Perioperative Outcomes of Index vs Nonindex Hospital Readmissions after Radical Cystectomy: Implications for Regionalization of Care

Abstract: Purpose-To compare the timing, causes, hospital costs, and perioperative outcomes of index vs. non-index hospital readmissions following radical cystectomy.Materials and Methods-The 2013 Nationwide Readmissions Database was queried for bladder cancer patients undergoing cystectomy. Sociodemographic characteristics, hospital costs, and causes of readmission were compared among index and non-index readmitted patients. Univariable and multivariable logistic regression models were used to identify predictors of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…In RC patients specifically, our present results align well with prior analyses of Medicare data that found GI, urinary, and infection amongst the most common readmissions diagnoses and that the highest intensity readmission episodes are more likely in patients with earlier, rapid readmissions [8,23]. Other recent work has shown that readmissions to hospitals other than that which performed the RC were more likely to occur later in the readmissions period, although this effect was predominantly observed after the 30 day period used in our present study [24]. Lastly, as readmissions have been linked to postoperative complications, it was recently demonstrated that the significant majority of these complications occur very early in the postoperative period [25].…”
Section: Discussionsupporting
confidence: 91%
“…In RC patients specifically, our present results align well with prior analyses of Medicare data that found GI, urinary, and infection amongst the most common readmissions diagnoses and that the highest intensity readmission episodes are more likely in patients with earlier, rapid readmissions [8,23]. Other recent work has shown that readmissions to hospitals other than that which performed the RC were more likely to occur later in the readmissions period, although this effect was predominantly observed after the 30 day period used in our present study [24]. Lastly, as readmissions have been linked to postoperative complications, it was recently demonstrated that the significant majority of these complications occur very early in the postoperative period [25].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the NCDB is not population‐based or designed to create national estimates and only includes unplanned readmissions within 30 days to the index institution . We have previously shown that almost one‐third of all readmissions after RC are at non‐index hospitals, suggesting that many admissions may be missed within the NCDB . The NRD, in contrast, includes readmissions up to 90‐days follow‐up and those at non‐index hospitals within the same State of treatment, making it a better estimate of national readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary diversion was defined as incontinent (ileal conduit, 56.51, 56.71) or continent (orthotopic neobladder or continent cutaneous reservoir, 57.87). The current ICD‐9 coding schema does not differentiate between orthotopic neobladder or continent cutaneous reservoir, so these were included together as continent diversions, similar to previous studies . We elected to only compare those patients with a bowel diversion and thus patients with a ureterocutaneostomy were not included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations